Enhanced Performance Of Multi-Stage Anaerobic Digestion Of Tofu Wastewater: Role Of Recirculation - Hanny Vistanti; Rizal Awaludin Malik (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2019)
Continuous three-stage anaerobic reactors with recirculation system were employed to treat real tofu wastewater. The system consists of 3 reactors connected in series and effluent of the last reactor was partly returned as feed of the first reactor along with fresh wastewater. The recirculation system was conducted on four variations of recirculation ratio (RR)s of 0, 1.0, 1.3, and 1.5 to evaluate the influence of recirculation on stability and performance of anaerobic system. Results showed that recirculation improved the performance of anaerobic digestion. COD was fluctuated without recirculation and gradually decreased to 373 and 298 mg/L at RR 1.3 and 1.5, respectively. Likewise, pH value was dropped to 6.5 at RR 0, and started to increase to approximately 8.0 upon employing recirculation. In addition, the system also showed excellent toleration against rise in ammonia loading, with effluent ammonia approximately 4.678 mg/L. The findings showed that the system employed had excellent efficiency and stability in treating tofu wastewater.